Energy Harvesting and Power Management - Patel, Shwetak; Hodges, Steve; Paradiso, Joseph (IEEE Pervasive Computing Magazine, 2016)
Although research to improve the energy density of batteries continues to be a high priority, it's often also possible for users to employ other approaches to extend the battery lifetime of mobile devices, wireless sensors, and the like. Two key areas in this regard are energy harvesting and power management. The articles in this special issue cover a range of current research in the areas of energy harvesting, power management, and energy storage.